Teaching the History of Technical Communication: A Lesson with Franklin and Hoover - Todd, Jeff (Journal of Technical Writing and Communication, 2003)
The first part of this article shows that research in the history of technical communication has increased in quantity and sophistication over the last 20 years. Scholarship that describes how to teach with that information, however, has not followed, even though teaching the history of the field is a need recognized by several scholars. The article provides and defends four guidelines as a foundation to study ways to incorporate history into classroom lessons: 1) maintain a continued research interest in teaching history; 2) limit to technical rather than scientific discourse; 3) focus on English-language texts; and 4) focus on American texts, authors, and practices. The second part of the essay works within the guidelines to show a lesson that contrasts technical texts by Benjamin Franklin and Herbert Hoover. The lesson can help students see the difference in technical writing before and after the Industrial Revolution, a difference that mirrors their own transition from the university to the workforce.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjE5MC90Z2M4LWdidjktM2ozdC1rcjAw